Recent progress in understanding the interaction between ENSO and the East Asian winter monsoon: A review - Ma, Tianjiao; Chen, Wen (Frontiers in Earth Science, 2023)
This paper reviews recent advances in understanding the interaction between the East Asian winter monsoon (EAWM) and El Niño–Southern Oscillation (ENSO). The achievements are summarized into two aspects: (1) the impacts of ENSO on the EAWM, and (2) effects of the EAWM on ENSO. For the first aspect, the results show that: the current climate model simulations of ENSO impacts on the EAWM have a common weaker bias than in the observations; The influence of central Pacific type ENSO on the EAWM is generally weaker than that of the eastern Pacific type ENSO; The precipitation anomalies in the tropical Indian Ocean tend to contribute to the intra-seasonal transition of ENSO teleconnection over East Asia; The ENSO-EAWM relationship is unstable and subject to nonlinear modulation by the state of oceans and extratropical atmospheric phenomena, which include the Pacific Decadal Oscillation and the Arctic Oscillation. Regarding the second aspect, studies have shown that the “pure” EAWM (denoted as EAWMres), which is independent of the ENSO signal, can lead to significant variations in the tropical convection over the western Pacific, the local Hadley circulation over East Asia, and the Walker circulation over the equatorial latitudes; The CMIP6 models can preproduce the above EAWMres effects well, although with some weaker bias. The changes in tropical convection and extratropical zonal flow associated with the EAWMres tend to have a significant modulating effect on the ENSO atmospheric teleconnection over North America. A strong EAWM and a strong Australian summer monsoon coherently provide favorable conditions for the onset of El Niño.